PERBANDINGAN TINGKAT KEPADATAN TANAH DI LIMA KECAMATAN KOTA PAYAKUMBUH DENGAN METODA STANDAR PROKTOR - Asnur, Hanifah; Yunita, Rini (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Payakumbuh is an area traversed by three rivers, namely the Batang Agam River, Batang Lampasi Riverand Batang Sinamar River, therefore the city of Payakumbuh has the nature and type of soil rather soft and contains a lot of water, so that in order to carry out the development it is necessary to carry out soil testing. one is testing about soil density with proctor standart test. Soil density testing was carried out in five sub-districts of Payakumbuh city in order to obtain the maximum density value g D Max and optimum water content W opt, while the test results obtained are as follows: South Payakumbuh sub-district: g D Max = 1.48 t/m3 and W opt = 10.12 %, North Payakumbuh District : g D Max = 1.72 t/m3 and W opt = 11.90 %, West Payakumbuh District : g D Max = 1.69 t/m3 and W opt = 14 .23 %, Payakumbuh Timur sub-district: g D Max = 1.65 t/m3 and W opt = 10.12 %, Latina sub-district: g D Max = 1.82 t/m3 and W opt = 16 % From the test data It can be seen that the highest density level is Latina sub-district with a maximum density value of 1.82 t/m3 and an optimum water content of 16%.